Engineering Education and Management Vol 1, Results of the 2011 International Conference on Engineering Education and Management (ICEEM2011) - Zhang, Liangchi; Zhang, Chunliang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This is the proceedings of the selected papers presented at 2011 International Conference on Engineering Education and Management (ICEEM2011) held in Guangzhou, China, during November 18-20, 2011. ICEEM2011 is one of the most important conferences in the field of Engineering Education and Management and is co-organized by Guangzhou University, The University of New South Wales, Zhejiang University and Xi$1 (Ban Jiaotong University. The conference aims to provide a high-level international forum for scientists, engineers, and students to present their new advances and research results in the field of Engineering Education and Management. This volume comprises 121 papers selected from over 400 papers originally submitted by universities and industrial concerns all over the world. The papers specifically cover the topics of Management Science and Engineering, Engineering Education and Training, Project/Engineering Management, and Other related topics. All of the papers were peer-reviewed by selected experts. The papers have been selected for this volume because of their quality and their relevancy to the topic. This volume will provide readers with a broad overview of the latest advances in the field of Engineering Education and Management. It will also constitute a valuable reference work for researchers in the fields of Engineering Education and Management.s
From the content: Dimensions of Perceived Risk and Their Influence on Consumers$1 (BPurchasing Behavior in the Overall Process of B2C -- Research on the Mode Selection of Technology Transfer and Innovative Process -- ARCH Model Approach to Measuring Function of Government in the Science & Technology Auto-organization System -- Research on New Patterns of Fostering the Innovative Ability in China$1 (Bs Graduate Education -- Social Network$1 (Bs Impact on New Venture Performance - An Empirical Research of Zhejiang Entrepreneurs.s
Keywords: Engineering; Education; Engineering economy; System safety; Engineering; Engineering Economics, Organization, Logistics, Marketing; Educational Technology; Quality Control, Reliability, Safety and Risk